Characterization of poly(lactic acid)s with reduced molecular weight fabricated through an autoclave process. (July 2017) - Behera, Kartik; Chang, Yen-Hsiang; Chiu, Fang-Chyou; Yang, Jen-Chang
Abstract: Poly(lactic acids) (PLAs) with different molecular weights (MWs) were prepared by autoclaving a commercial PLA for different time periods. The harvested PLAs were characterized by different techniques. Gel permeation chromatography results showed that the MW of PLA decreased with increasing autoclaving time. The Mark–Houwink parameters for PLA in dichloromethane at 25 °C were determined for the first time. The melting endotherms, revealed by differential scanning calorimetry, were observed for the 60 and 120 min-autoclaved PLAs (cf. PLA60 and PLA120) but hardly detected for the original and 30 min-autoclaved PLA (PLA30). The PLA120 exhibited higher crystallinity than that of PLA60. Thermogravimetric analysis showed that the activation energy for thermal degradation decreased from 186 kJ mol −1 to 140 kJ mol −1 for original PLA and PLA120. The hydrophilicity of the PLA increased, indicating higher number of COOH groups, with increasing autoclaving time, as revealed by the contact angle measurement. Rheological data showed that the complex viscosity and storage modulus of PLA decreased with increasing autoclaving time due to the decreasing MW. Unlike original PLA and PLA30, PLA60 and PLA120 exhibited Newtonian fluid behavior at all test frequencies.